Perspectives of applied emerging media in educators teaching method during COVID-19 pandemic - Arif Bahari Mohamed Musli; Mohd Hanafi Jumrah (Penerbit Universiti Kebangsaan Malaysia, 2021)
Due to COVID-19 pandemic, the largest disruption of education systems in history occured, affecting nearly 1.6 billion learners in more than 190 countries and all continents. Closures of schools and other learning institutions had impacted 94 per cent of the world’s student population, up to 99 per cent in low and lower-middle income countries. When the pandemic started both educators and students had to replace traditional teaching with online teaching. Educators had to adapt to new pedagogical concepts and modes of delivery of teaching. This research is to determine the perspectives of educators in using online teaching approaches and identify emerging media applied on online teaching. Diversity in teaching approach for effective teaching as a good method must be adopted by an educator. Educators look for new approaches of attracting students to distance learning and integration of media is one of them to deliver the education. This research was conducted using a qualitative method that is an interview with educators in Malaysia and the data will be analysed using thematic analysis. Two main findings have been obtained: i) Perspectives of online teaching during Covid-19 Pandemic and ii) Applied of emerging digital media in online teaching. The study shows that the first main theme is the perspectives of educators in using online teaching approaches to divide into three main themes that are teaching technique, teaching tools and education management. The second theme is mixed digital media in online teaching like social media, video, audio visual, digital publishing, and digital information is used throughout online platforms. Online teaching more interactive learning has to be wide, open, easy access, and more sources to explore. The theory that is the strongest in supporting this study is The Unified Theory of Acceptance and Use of Technology (UTAUT) contains the key areas which are 1) performance expectancy, 2) effort expectancy, 3) social influence, and 4) facilitating conditions.